1984
DOI: 10.1287/opre.32.4.917
|View full text |Cite
|
Sign up to set email alerts
|

Extensions of the Freund Distribution with Applications in Reliability Theory

Abstract: The Freund distribution models situations in which the exponential residual lifetime of one component depends on the working status of another component. The literature has discussed generalizations and analogs of the Freund distribution. Such generalizations can be obtained by replacing exponential random variables by Weibull or gamma random variables, or by compounding (mixing) Freund distributions. This paper shows how to unify various well-known generalizations of the Freund distribution by using one simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It can be shown in this case (see [6]) that the time of system failure has the stronger than NBU property of being an increasing failure rate on average (IFRA) distribution. We do not know if this result can be extended to the case n > 2.…”
Section: P{t > S + T I T > S} T)mentioning
confidence: 92%
“…It can be shown in this case (see [6]) that the time of system failure has the stronger than NBU property of being an increasing failure rate on average (IFRA) distribution. We do not know if this result can be extended to the case n > 2.…”
Section: P{t > S + T I T > S} T)mentioning
confidence: 92%
“…An extension to a model with Weibull component lifetime distributions was discussed in Lu, Spurrier and Weier, and Shaked . In Asha et al, a generalization of was proposed as follows.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, various specific parametric models for bivariate distributions have been suggested and studied. See, for instance, Gumbel (1960), Freund (1961), Marshall and Olkin (1967), Downton (1970), Hawkes (1972), Block and Basu (1974), Shaked (1984), Sarkar (1987) and Hayakawa (1994). A nice review on the modelling of multivariate survival models can be found in Hougaard (1987).…”
Section: Introductionmentioning
confidence: 99%